Retino‐dural hemorrhages in infants are markers of degree of intracranial pathology, not of violent shaking - Chris Brook (Annals of the Child Neurology Society)
Abstract Aim This study analyzed whether retino‐dural hemorrhages in infants are markers of the degree of intracranial pathology, rather than evidence of violent shaking. Methods Using data from 420 infants with acute intracranial pathologies, comparison of clinical findings is made between cases diagnosed as abusive head trauma (AHT) and four categories: cases where caregivers report no trauma; cases of witnessed or admitted AHT; cases where caregivers report accidental trauma; and witnessed accidents. The data are then controlled for degree of intracranial pathology by only comparing cases in each category that have evidence of hypoxic‐ischemic swelling. Results Although categories differ in clinical findings when all data are considered, they do not differ when the data are controlled for degree of intracranial pathology. Conclusions The data suggest that the clinical findings widely considered to be indicative of shaking are instead markers of the degree of intracranial pathology. Previous results showing differences were driven by selection effects, whereby different categories have different fractions of serious cases. Most notably, caregiver and witnessed reports of accidental head trauma led doctors to explore intracranial pathologies across a broader spectrum of severity, including milder cases, as opposed to situations where no head trauma is reported.